Induction pegylated interferon Alfa-2a and high dose ribavirin do not increase SVR in heavy patients with HCV genotype 1 and high viral loads - Reddy, K. Rajender; Shiffman, Mitchell L.; Rodrigueztorres, Maribel; Cheinquer, Hugo; Abdurakhmanov, Djamal; Bakulin, Igor; Morozov, Viacheslav; Silva, Giovanni Faria [UNESP]; Geyvandova, Natalia; Stanciu, Carol; Rabbia, Michael; McKenna, Michael; et al. (Elsevier, 2010)
Background & Aims Patients infected with hepatitis C virus (HCV) genotype 1, body weight <85 kg, and high baseline viral load respond poorly to standard doses of pegylated interferon (peginterferon) and ribavirin. We evaluated intensified therapy with peginterferon alfa-2a plus ribavirin. Methods This double-blind randomized trial included HCV genotype 1-infected outpatients from hepatology clinics with body weight <85 kg and HCV RNA titer <400,000 IU/mL. Patients were randomized to 180 μg/wk peginterferon alfa-2a for 48 weeks plus 1200 mg/day ribavirin (standard of care) (group A, n = 191) or 1400/1600 mg/day ribavirin (group B, n = 189). Additional groups included 360 μg/wk peginterferon alfa-2a for 12 weeks then 180 μg/wk peginterferon alfa-2a for 36 weeks plus 1200 mg/day ribavirin (group C, n = 382) or 1400/1600 mg/day ribavirin (group D, n = 383). Follow-up lasted 24 weeks after treatment. Results Sustained virologic response rates (HCV RNA level <15 IU/mL at end of follow-up) in groups A, B, C, and D were 38%, 43%, 44%, and 41%, respectively. There were no significant differences among the 4 groups or between pooled peginterferon alfa-2a regimens (A + B vs C + D: odds ratio [OR], 1.08; 95% confidence interval [CI], 0.831.39; P = .584) or pooled ribavirin regimens (A + C vs B + D: OR, 1.00; 95% CI, 0.791.28; P = .974). Conclusions In patients infected with HCV genotype 1 who are difficult to treat (high viral load, body weight <85 kg), a 12-week induction regimen of peginterferon alfa-2a and/or higher-dose ribavirin is not more effective than the standard regimen. © 2010 AGA Institute.
Keywords: Chronic Hepatitis C; Steatosis and Response to HCV Therapy; Tolerability of High-Dose Pegylated Interferon; Tolerability of High-Dose Ribavirin; colony stimulating factor; peginterferon alpha2a; ribavirin; virus RNA; adult; alopecia; anemia; arthralgia; asthenia; body weight; chill; clinical trial; controlled clinical trial; controlled study; coughing; decreased appetite; depression; diarrhea; dizziness; double blind procedure; drug dose reduction; drug efficacy; drug eruption; drug fever; drug induced headache; drug megadose; drug withdrawal; fatigue; female; follow up; genotype; hemoglobin blood level; hepatitis C; human; insomnia; irritability; major clinical study; male; mediastinum disease; multicenter study; myalgia; nausea; neutrophil count; outpatient; pneumonia; priority journal; pruritus; randomized controlled trial; respiratory tract disease; side effect; thorax disease; thrombocyte count; treatment duration; virus load; Adult; Antiviral Agents; Body Weight; Dose-Response Relationship, Drug; Drug Therapy, Combination; Fatty Liver; Female; Genotype; Hepacivirus; Hepatitis C, Chronic; Humans; Interferon Alfa-2a; Male; Middle Aged; Obesity; Polyethylene Glycols; Ribavirin; Viral Load